Evidence of a causal relationship between blood pressure and pathological scars: a bidirectional Mendelian randomization study - Du, Dan; Li, Jiaqi; Jiang, Xian (Frontiers in Medicine, 2024)
Background Recent advancements in basic medicine and epidemiology suggest a potential influence of blood pressure on scar formation, yet the specifics of this relationship are not fully understood. This study aims to clarify the causal link between blood pressure and the development of pathological scars using Mendelian randomization (MR). Methods This study employed genetic variants closely linked to blood pressure as instrumental variables to explore the relationship between blood pressure and pathological scars. The inverse variance weighted (IVW) method was used for analysis. Results Our analysis identified a notable association where higher blood pressure was correlated with a lower risk of pathological scars. Specifically, an increase in diastolic blood pressure (odds ratio [OR] per standard deviation increase: 0.67 [95% Confidence Interval [CI], 0.49–0.99]), systolic blood pressure (OR per standard deviation increase: 0.66 [95% CI, 0.46–0.93]), and hypertension (pooled OR: 0.39 [95% CI, 0.18–0.85]) were significantly associated with a reduced risk of keloids. Similarly, a genetic predisposition to hypertension (pooled OR: 0.31 [95% CI, 0.11–0.89]) was significantly associated with a reduced risk of hypertrophic scars. Neither reverse MR analysis nor Steiger’s test indicated a significant reverse causal relationship between hypertension and either keloids or hypertrophic scars. Conclusion The findings suggest a protective role of higher blood pressure against the development of pathological scars, including keloids and hypertrophic scars. However, the inconsistency observed across different MR methods warrants cautious interpretation and underscores the need for further investigation to confirm these findings.